Development of engineered cementitious composites/strain-hardening cementitious composites (ECC/SHCC) with waste granite fine powders - Li, Ziyang (2024)
In this study, a sustainable Engineered Cementitious Composites/Strain-hardening Cementitious Composite (ECC/SHCC) mixture with the replacement of standard sand (SS) by an industrial waste material granite fine (GF) was developed. A thorough evaluation of mechanical properties, including compressive strength, tensile strength, and matrix toughness, was conducted to examine the feasibility and potential of the newly developed GF-ECC/SHCC. The introduction of GF is critical to enhance the tensile performance of ECC/SHCC, revealing a significant advancement over the existing formulations. Additionally, the intricate interplay between the rheological and mechanical properties has been revealed in this research, effectively linking material flow behavior to its tensile performance. By characterizing the morphology and microstructure of raw materials and hydration products, this study illustrates GF's complex impacts at both macro and micro levels. The single-fiber pullout test and the fiber-bridging constitutive model of ECC/SHCC were applied to evaluate the effect of GF on the fiber-bridging behavior of the developed GF-ECC/SHCC mixtures. Although with up to 10% matrix compressive strength loss and higher superplasticizer dosages, the replacement of SS by GF efficiently improved the strain-hardening capacity and the ultimate tensile strength of the mixtures. This critical insight confirms GF is an effective substitute for SS in ECC/SHCC materials, ultimately enhancing performance across various parameters.